Top 10 tech cars [fuel efficient cars]. - Voelcker, J. (IEEE spectrum)
There are two groups within the global automobile industry that are competing to develop the most fuel efficient car. On one hand are the US and Japanese manufacturers who have invested billions of dollars in hybrid electric technology, while on the other hand are the European makers who support light-duty diesel engines. In addition to fuel efficiency, car manufacturers are working to provide more high-tech features in the passenger compartment including interfaces for the iPod, high definition radio, and advanced navigation systems. Although self-driving cars in showrooms are still a few years away, there are significant milestones in that direction such as the 2007 Lexus sedan which is able to park itself with minimal help from the driver.